Amidated and Ibuprofen-Conjugated Kyotorphins Promote Neuronal Rescue and Memory Recovery in Cerebral Hypoperfusion Dementia Model - Sá Santos, Sónia; Santos, Sara M.; Pinto, Antónia R. T.; Ramu, Vasanthakumar G.; Heras, Montserrat; Bardaji, Eduard; Tavares, Isaura; Castanho, Miguel A. R. B. (Frontiers in Aging Neuroscience, 2016)
Chronic brain ischemia is a prominent risk factor for neurological dysfunction and progression for dementias, including Alzheimer’s disease (AD). In rats, permanent bilateral common carotid artery occlusion (2VO) causes a progressive neurodegeneration in the hippocampus, learning deficits and memory loss as it occurs in AD. Kyotorphin (KTP) is an endogenous antinociceptive dipeptide whose role as neuromodulator/neuroprotector has been suggested. Recently, we designed two analgesic KTP-derivatives, KTP-amide (KTP-NH2) and KTP-NH2 linked to ibuprofen (IbKTP-NH2) to improve KTP brain targeting. This study investigated the effects of KTP-derivatives on cognitive/behavioral functions (motor/spatial memory/nociception) and hippocampal pathology of female rats in chronic cerebral hypoperfusion (2VO-rat model). 2VO-animals were treated with KTP-NH2 or IbKTP-NH2 for 7 days at weeks 2 and 5 post-surgery. After behavioral testing (week 6), coronal sections of hippocampus were H&E-stained or immunolabeled for the cellular markers GFAP (astrocytes) and NFL (neurons). Our findings show that KTP-derivatives, mainly IbKTP-NH2, enhanced cognitive impairment of 2VO-animals and prevented neuronal damage in hippocampal CA1 subfield, suggesting their potential usefulness for the treatment of dementia.